2011
DOI: 10.1002/bjs.7532
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the toll-like receptor 9 gene associated with sepsis and multiple organ dysfunction after major blunt trauma

Abstract: TLR9 polymorphisms rs187084 and rs352162 might be used to provide relevant risk estimates for the development of sepsis and MOD in patients with major trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 18 publications
1
16
0
6
Order By: Relevance
“…In addition to the abovementioned effect of rs5743836 on transcription factor binding,14 certain rs352162 alleles have been associated with an increased TNFα production by peripheral blood leucocytes in response to bacterial DNA stimulation 32. Yet, analysis of the exact functional consequences of the AAV-associated TLR9 polymorphisms appears mandatory before any further clues for AAV pathology can be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the abovementioned effect of rs5743836 on transcription factor binding,14 certain rs352162 alleles have been associated with an increased TNFα production by peripheral blood leucocytes in response to bacterial DNA stimulation 32. Yet, analysis of the exact functional consequences of the AAV-associated TLR9 polymorphisms appears mandatory before any further clues for AAV pathology can be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown TLR9 polymorphisms to be associated with CD and specific TLR9 polymorphisms to be associated with altered TNFα and/or IFNγ levels [14], [15], [16], [17]. In addition, one study has shown interactions between TLR9 polymorphisms and NOD2 variants in patients with CD [18].…”
Section: Resultsmentioning
confidence: 99%
“…Cells that express TLR9, which include plasmacytoid dendritic cells (pDCs) and B cells, produce cytokines, chemokines and interferons (27). The TLR9 variant examined in this study has been shown to be associated with chronic inflammatory conditions like Systemic Lupus Erythematosus (SLE), Crohn’s (28) disease and cervical cancer (29) where abnormal sensitization of the immune system by microbial agents plays a role in disease evolution.…”
Section: Discussionmentioning
confidence: 99%